Evaluation of local, high yielding and hybrid transplanted aman rice varieties for phenology, grain morphology and yield - Sarkar, Mohammad Joyel; Hasan, Ahmed Khairul; Islam, Najrul; Yasmine, Fahmina; Islam, Shams Shaila; Rashid, Md Harun (Fundamental and Applied Agriculture, 2021)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University during the period from June to December 2016 to evaluate local, high yielding and hybrid transplanted aman rice varieties for grain morphology and grain yield. The experiment was comprised of 15 transplanted aman (T. aman) rice varieties viz., high yielding varieties (HYV): BR11, BRRI dhan34, BRRI dhan38, BRRI dhan49, BRRI dhan52, BRRI dhan56, BRRI dhan62, Binadhan-7, Binadhan-12, Binadhan-13; local varieties: Balam, Kalizira, Nizersail, Bashiraj; and hybrid variety: Agro dhan-12. Duration of the phenological events such as date of emergence of seedlings, booting, heading, anthesis, physiological maturity and total growth duration was higher in local varieties compared to high yielding and hybrid. The lowest duration of these events were recorded in BRRI dhan62 and BRRI dhan56. The tallest plant was obtained from local variety Kalizira (167.27 cm) and the shortest one was obtained from HYV BRRI dhan56 (105.20 cm). Hybrid variety Agro dhan-12 possessed the highest number of effective tillers hill−1 (17.0) which was similar to HYV BRRI dhan49 (17.0) and the lowest number was recorded in HYV BRRI dhan38. Number of grains panicle−1 was the highest in hybrid variety Agro dhan-12 (235) and the lowest was present in local variety Balam. Thousand grain weight was highest at hybrid variety Agro dhan-12 (35 g) and the lowest one was observed in BRRI dhan34 (12.07 g). Grain yield was highest in hybrid variety Agro dhan-12 (6.50 t ha−1) which was similar to high yielding varieties BRRI dhan49 (6.0 t ha−1). In lower part of panicle, primary and secondary grain length (L), breadth (B), volume, L/B ratio was maximum in Binadhan-7 and Agro dhan-12. In middle part of the panicle, primary and secondary grain length, volume was found the maximum in Binadhan-7 and breadth was maximum in BR11, Agro dhan-12. Height was maximum in BRRI dhan56. In upper part of the panicle, primary and secondary grain length and volume was maximum in Binadhan-7 and breadth was maximum in Agro dhan-12 and height was maximum in BRRI dhan52.